The activity of Na+, K+-ATPase and adenine nucleotides content in the heart muscle of rats under conditions of combined effect of ionizing radiation and intense physical exercise - Ye. Dubna; L. Tereshchenko; A. Vasіlieva (Journal of Education, Health and Sport)
There is a high risk of radiation contamination of the environment due to warfare taking place on the territory of Ukraine. The impact of ionizing radiation on the body is often combined with heavy physical exertion, which significantly exacerbates its negative effects. Many systems of the living organism become compromised and in particular the cardiovascular system. Therefore, the aim of this article is to study the active ion transport systems functioning and the adenine nucleotides content in the mitochondrial fraction of the heart muscle from irradiated rats subjected to intense physical exercise.